Applying Strict Liability for Environmental Offenses: Indonesian Perspective (Medico Legal Update, 2021)
This study aims to analyze the rationality and application of strict liability for environmental offenses in theEnvironmental Protection and Management Act of Indonesia. The strict liability set out in this law expresslyapplies only to civil cases and covers the possibility that it may be used in criminal matters. Normativelegal research complemented by a statutory and conceptual approach was used. The results showed that itgenerally applies to regulatory offenses aimed at protecting the public interest. This doctrine is necessaryto improve the long-term and prevents harm to people or the environment. The absence of mental elementproof should be limited to offenses that are characterized by the administrative dependence of criminallaw, which is reflected in the abstract and concrete endangerment models. Generally, prohibited behaviorrelated to waste/emissions disposed into the environment without approval causes damage. The offense isformulated as formal offense by eliminating the element of the perpetrator’s culpability, and it is thereforenot necessary to prove it.